The Impact of Digital Transformation on SME Growth in Emerging Economies - Arlin Ferdin Gulo; Ratih Eka Kusumawati (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
This study investigates the influence of digital transformation on the growth and competitiveness of small and medium enterprises (SMEs) in emerging economies. Using a mixed-method approach, the research explores how digital tools improve operational efficiency, market access, and customer engagement. Findings highlight that while digital adoption increases profitability, challenges such as technological gaps and regulatory barriers persist. The study offers practical recommendations for policymakers and business owners to enhance digital readiness.